Evaluation of a Peer Led Chronic Pain Self-Management Program in a Rural Population. (September 2022) - Pullyblank, Kristin; Brunner, Wendy; Scribani, Melissa; Krupa, Nicole; Wyckoff, Lynae; Strogatz, David
Background: The Chronic Pain Self-Management Program is an evidence-based intervention that has been shown to be efficacious in reducing symptoms of chronic pain. However, there is a paucity of research examining CPSMP in a predominantly rural population. The purpose was to evaluate patient-reported outcomes of in-person peer-led CPSMP workshops offered in a rural region in 2018 and 2019. Methods: Participants were surveyed at baseline and 6 months post-workshop. Descriptive statistics were used to describe characteristics of CPSMP completers. Paired t-tests were used to analyze change in depression score (PHQ-8), disability (modified Roland-Morris Disability Questionnaire), self-efficacy, and patient activation (PAM-10). Analysis of variance was used to detect differences over time by age group, education, insurance type, self-rated health, and comorbidities. Results: Among the 327 adults who enrolled in a workshop, 73.1% completed. Of completers, 74.9% were female, average age was 65. Significant improvements were observed in pain disability ( P = .0008), patient activation ( P = .0362), depression ( P < .0001), and self-efficacy ( P < .0001), at 6 weeks; and pain disability ( P = .0030), depression ( P = .0015), and self-efficacy ( P = .0064) at 6 months post-program. Individuals who rated their health as fair/poor at baseline reported greater improvements in depression scores than individuals who rated their health as good or better ( P < .0002). There were also distinct patterns of change in pain disability among the different age groups. No other differences between groups were noted. Conclusions: The CPSMP appears to improve pain self-efficacy, disability, and depression regardless of age, gender, insurance status, education, or comorbidities. Healthcare and community organizations should consider investing in and offering chronic pain workshops in rural areas in order to promote health and wellness.